Automação de processo de obtenção de biodiesel em plantas de pequeno porte, utilizando controlador lógico programável - Macedo, Humberto Rodrigues. (Universidade Federal do Tocantins, 2020)
The automatic control biodiesel production process contributes to the quality and homogeneity of the final product and for the liberation of man from unhealthy jobs. This work proposes a model of automatic biodiesel production plant and its control system for small plants. Research was carried out on the processes of obtaining biodiesel to propose an automatic plant model. A Power system 3000 automation case containing a SIMATIC S7- 1214C CLP, sensors and actuators was used to simulate the operation of the plant prototype. In order to prove the operation of the plant automation, the supervisor screen of the plant was developed with the software Elipse E3 Studio in the demo version. As a result, obtained a plant and automation project that pre-mixes the alcohol with the catalyst; performs cycles of washing biodiesel in the amount previously reported and makes the automatic separation between biodiesel and glycerin. Both the plant model and the programming and control model can be adapted to different production capacities. The cost estimate with the automation process was of R$ 11,118.47 for application in new plants. This value may be reduced in cases of adaptations existing manual or semiautomatic plants